2015
DOI: 10.1097/qai.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Infants Starting Antiretroviral Therapy in Southern Africa, 2004–2012

Abstract: Background There is limited published data on the outcomes of infants starting antiretroviral therapy (ART) in routine care in Southern Africa. This study aimed to examine the baseline characteristics and outcomes of infants initiating ART. Methods We analysed prospectively collected cohort data from routine ART initiation in infants from 11 cohorts contributing to the International Epidemiologic Database to Evaluate AIDS in Southern Africa. We included ART naïve HIV-infected infants <12 months of age initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 31 publications
7
37
0
Order By: Relevance
“…The results were consistent with those from larger studies in similar cohorts. [13,14] It has also shown important negative outcomes associated with the down-referral process, with 18.9% of the study cohort LTFU, 50.0% of whom never presented to PHC clinics, and a further 11.4% having >8 weeks between down-referral and presentation to PHC clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were consistent with those from larger studies in similar cohorts. [13,14] It has also shown important negative outcomes associated with the down-referral process, with 18.9% of the study cohort LTFU, 50.0% of whom never presented to PHC clinics, and a further 11.4% having >8 weeks between down-referral and presentation to PHC clinics.…”
Section: Discussionmentioning
confidence: 99%
“…For the 99 children who were admitted to hospital, the mean (SD) length of stay was 19 (14) days and the most common admission diagnoses were acute lower respiratory tract infection (52.5%) and diarrhoeal disease (36.4%). Most of the children were managed in general medical or acute short-stay wards (70.2%).…”
Section: Hiv Diagnosis and Hospitalisationmentioning
confidence: 99%
“…For women considering PrEP use in pregnancy, these uncertain risks must be weighed against the increased risk of HIV acquisition during pregnancy and the subsequent increased risk of perinatal transmission during acute HIV infection. Observational analyses suggest that pregnancy-induced immune, hormonal, and behavioral changes may increase HIV susceptibility and acute HIV infection during pregnancy has significant consequences for the baby and mother [1, 2, 37-39]. Acute HIV infection during pregnancy and postpartum poses a double burden as acute maternal HIV infection accounts for 26% of perinatal HIV transmission [40, 41].…”
Section: Should Peri-conception Prep Used By Women Be Continued Durinmentioning
confidence: 99%
“…Current guidelines recommend treatment of infants immediately upon a diagnosis of HIV infection, and treatment according to these guidelines has been associated with good clinical outcomes (6,7). Nevertheless, an analysis of children treated in South Africa showed that the probability of virological suppression at age 12 months was only 56% (8). This may be due to the higher viral loads and challenges associated with accurate dosing in infants, placing them at a potentially greater risk for developing PI drug resistance than adult patients (9).…”
mentioning
confidence: 99%